Transition-metal-free synthesis of quinolines from 2-nitrobenzyl alcohol in water. Issue 48 (2nd December 2015) - Zhu, Meijuan; Wang, Chao; Tang, Weijun; Xiao, Jianliang
Graphical abstract: Abstract: A method for the synthesis of quinolines from cheap and readily available 2-nitrobenzyl alcohol without a transition-metal catalyst in water has been developed, providing a convenient method for accessing quinolines. The reaction features an intramolecular redox process, which generates the key intermediate leading to product formation.